1972
DOI: 10.1159/000192897
|View full text |Cite
|
Sign up to set email alerts
|

Über den Einfluss langjährigen Zigarettenrauchens auf die Lungenfunktion jugendlicher Normalpersonen

Abstract: Spirometric and plethysmographic measurements combined with investigations of lung PV-characteristics by means of oesophageal catheters were carried out in both 20 young healthy smokers and 20 non-smokers. The mean age of all probands was 29 years. The following results were obtained: (1) Spirometric data andairway resistance were normal in all subjects. Viscous work of breathing, however, was significantly elevated in cigarette smokers. (2) The static elastic recoil pressures of all subjects fell within the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

1974
1974
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Smokers were expected to show a fall in compliance at increased respiratory rates (Ingram and O'Cain, 1971;Huttemann et al, 1972), but this finding was not confirmed in the larger number of subjects in this study. There was a slight excess of heavier smokers in the control group and six male volunteers were excluded from analysis for FDC because their FEV1 was less than 80% of predicted.…”
Section: Discussionmentioning
confidence: 66%
“…Smokers were expected to show a fall in compliance at increased respiratory rates (Ingram and O'Cain, 1971;Huttemann et al, 1972), but this finding was not confirmed in the larger number of subjects in this study. There was a slight excess of heavier smokers in the control group and six male volunteers were excluded from analysis for FDC because their FEV1 was less than 80% of predicted.…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, constituents of the tobacco present in the small airways [33] might bring about an alveolar underventilation with maintained perfusion owing to hypersecretion of mucus. However, even an appreciable increase in the airway resistance in the small airways is not reflected in the Raw [25], since the small airways only account for 10-30% of the overall airway resistance of the bronchial system [20,29,39,48]. We were unable to observe an alteration in the Cdyn40 after smoking as a possible indication for an increase in resistance in the small airways [20,39,48].…”
Section: Discussionmentioning
confidence: 68%
“…However, even an appreciable increase in the airway resistance in the small airways is not reflected in the Raw [25], since the small airways only account for 10-30% of the overall airway resistance of the bronchial system [20,29,39,48]. We were unable to observe an alteration in the Cdyn40 after smoking as a possible indication for an increase in resistance in the small airways [20,39,48]. The Cayn40 reacts congruently with the fall in Raw, but the rise was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Dieser Mittel wert hegt deutlich niedriger als der von 20 Nichtrauchern, der von Hüttemann et al [15] mit 3,58 g • cm/ml angegeben wurde. Die von die sen Autoren gefundene Standardabweichung von ±1,11 g • cm/ml ent spricht recht gut der unsrigen.…”
Section: Diskussionunclassified